Conducting RSD for resettlement: the need for procedural protections - Fisher, B (Refugee Studies Centre, University of Oxford, 2020)
Procedural protections are vital in all aspects of refugee status determination (RSD). Shortcomings in operations conducting RSD for purposes of access to resettlement and complementary pathways call for greater clarity and transparency.